Analysis of Cadets’ Skill in Envisaging Job Interview through Demonstration Method for Aircraft Maintenance Technology Aviation Polytechnic of Makassar - Masita, Maya (Universitas Cokroaminoto Palopo, 2023)
This article was based on the readiness of students to face job market in the future, especially considering the competition in getting jobs nowadays will be increasingly stringent. Automatically, the opportunity to get a decent job will be dwindling due to fierce competition of the job seekers. This research aims to (1) Knowing the ability of Aircraft Maintenance Technology cadets at the Makassar Aviation Polytechnic in answering job interviews through the demonstration method. (2) Knowing the Students’ perception on the application of the demonstration method in answering job interviews. The research conducted in this article was the application of the demonstration method to cadets/students in facing job interviews in the future. This research used a qualitative method in gaining the data. The research activity was carried out in three meetings using observation data and interviews as data collection instruments. Based on the results of the study, it was revealed that the abilities possessed by Aircraft Maintenance Technology cadets at the Makassar Aviation Polytechnic in answering job interviews through demonstration methods, namely the ability to English speaking, writing Curriculum Vitae (CV) and cover letters in English, and controlling themselves during interviews. As for the cadets' perception of the application of the demonstration method collected through interviews, it showed that the material and methods applied were in accordance with the needs of cadets.